THE BALINESE TRADITIONAL CULINAIR MUST BE SURVIVED AS A GREEN TOURISM TO PRESERVE SUSTAINABLE TOURISM - I Made Sudiarta (Institut Pariwisata dan Bisnis Internasional, 2016)
According to an International Magazine stated that Bali is the best of the world destination country, not famous only of the splendor of Bali and its unique culture, but also its culinair. (Bali Post, Nov 2015).Bali which is said to be the island of one thousand temples: Bali is the island of GODS; Bali is a paradise; also famous with various kinds of specific and typical traditional culinairs. (Sulistiyo, 2011, 94).This Balinese traditional culinair must be surfived as a green tourism to preserve sustainable tourism, to be able to be enjoyed by young generations (Picard, 1996, 64).This decision was committed during the audiency of Bali Post Newspaper Commity to PT. Sinar Sosro, the sales office of Bali & NUSRA Region, last Friday june 10th, 2016 just a few days ago. (Bali Post, June 2016).It is expected that by the frequently of culinair festival we can preserve sustainable tourism, and finally the Balinese Traditional Culinair could be surfived as a green tourism. (Bungin, 2007:87).